Myanmar’s Cultural Dimensions: Exploring The Relationship Among The Social Identity, Attitudes Towards Globalisation And Preferences Of Myanmar Consumers In Yangon - Rudkin, Alana; Erba, Joseph (Penerbit Universiti Sains Malaysia (USM Press), 2018)
Myanmar is transitioning to an open market economy, but very little is known about Myanmar consumers and their attitudes towards globalisation. Using Hofstede’s cultural dimensions and social identity theory, this study sheds light on the role Myanmar consumers’ cultural values and social identity play in consumer preferences. This study also explores the relationship between Myanmar identity and consumers’ perceptions of products based on country of origin and attitudes towards globalisation. Results from a cross-sectional survey of Myanmar consumers in Yangon (N = 268) reveal that consumers displayed cultural traits similar to the ones from their neighbouring Southeast Asian countries. In addition, Myanmar consumers in Yangon do not express any particular consumer animosity towards products from other countries and seem open to globalisation.